En velkjent soldat - en ukjent krig. Internasjonal høoring om søor-afrikas krigføoring mot nabolandene (1984)
A wellknown soldier - an unknown war; international hearing on South Africa's aggression against the neighbouring states in Oslo, 22-24 March 1984.